On the regularization method for Fredholm integral equations with odd weakly singular kernel - Noureddine Benrabia & Hamza Guebbai (Computational and Applied Mathematics, 2018)
In this paper, we propose a numerical method to approach the solution of a Fredholm integral equation with a weakly singular kernel by applying the convolution product as a regularization operator and the Fourier series as a projection. Preliminary numerical results show that the order of convergence of the method is better than the one of conventional projection methods.
https://doi.org/10.1007/s40314-018-0625-3